Implementasi Merdeka Belajar Dalam Pendidikan Seni Budaya Di Era Teknologi 4.0 - Saefurrohman, Nandi (CV. Multi Kreasi Media, 2023)
This study aims to explore and find out the application of the concept of independent learning carried out by cultural arts educators in the industrial era 4.0. The research uses a qualitative approach to obtain views and critical explanations of reality that appear as general symptoms, related to the rollout of the independent learning curriculum policy which is considered to improve the quality of arts and culture education in the midst of the ongoing development of information technology. The results showed that cultural arts educators in the face of independent learning were quite enthusiastic, although they still felt various obstacles, especially in understanding the concept of the actual independent learning curriculum, as well as learning methods that were considered able to adjust to current developments in information technology. Cultural arts educators have tried to develop a more advanced cultural arts learning process through the application of art learning models that are more plexible.